Canuck rock : a history of Canadian popular music - Edwardson, Ryan, 1974- (University of Toronto Press, 2009)
An invaluable resource and an absorbing read, Canuck Rock spans from the emergence of rock and roll in the 1950s through to today's international recording industry.